A comprehensive review on green synthesis of nature-inspired metal nanoparticles: Mechanism, application and toxicity. (1st November 2020) - Rana, Anu; Yadav, Krishna; Jagadevan, Sheeja
Abstract: Nanoparticles have emerged as one of the most sought-after materials finding application in various sectors. Synthesis of green nanoparticles have attracted extensive interest worldwide because of its biocompatibility and huge potential for utilization as catalysts, antimicrobial agents, in energy harvesting, cancer/gene therapy, sensing etc. Inherent properties of nano-materials such as specific size, shape, composition, greater surface area to volume ratio and purity of individual constituents makes it a fascinating multifunctional material. Diverse groups of living organisms (prokaryotes and eukaryotes) and biomolecules are increasingly being employed as bio-template for designing nanoscale materials. Characterization tools such as SEM, TEM, AFM, FTIR, XRD, NMR aid in unravelling their unique properties. This review provides a comprehensive overview of key findings in green synthesis of nanoparticles and attempts to determine their possible synthesis mechanism. This article also focuses on factors affecting their synthesis, characterization, applications, potential toxic impact on living organisms, merits/demerits and future prospects. Graphical abstract: Image 1 Highlights: This review highlights the methods for green synthesis of metal nanoparticles. Potential mechanisms involved in their synthesis are discussed. Environmental factors affecting the synthesis of green nanoparticles is analysed. Toxicity exhibited by green nanoparticles is also covered. Future perspectives and their potential applications are proposed.